Efektifitas Penggunaan Buku “Diari Gigi Sehat” terhadap Perilaku Orang Tua dalam Menjaga Kebersihan Gigi dan Mulut Anak Di Pontianak - Yeni Maryani; Pawarti Pawarti; Asmaul Husna; M Ibraar Ayatullah (Poltekkes Kemenkes Padang, 2022)
Mother is an important factor in maintaining the cleanliness of the child's teeth and mouth. For this reason, mothers need media to increase their knowledge. This study aims to determine changes in the behavior of mothers in maintaining the health of their children's teeth and mouth by using the book